6.4
(a) Start from
µ
∂
∂µ
=−
−
F
H
G
I
K
J
L
N
M
O
Q
P
⇒=
−
−
F
H
G
I
K
J
L
N
M
O
Q
P
11
C
VT
V
T
CV
T
V
T
PP
P
P
but
V
T
T
T
−
F
H
G
I
K
J
L
N
M
O
Q
P
F
H
G
I
K
J
2
a
f
and
C
TV
T
T
P
P
=
F
H
G
I
K
J
2
a
f
.
(b)
T
C
T
P
a
f
F
H
G
I
K
J
=
P
2
; integrate
V
T
V
T
C
T
dT
TP
F
H
I
K
−
F
H
I
K
=
z
21
1
2
2
,,
,
,
P
.
Thus
VT P
T
T
T
C
T
dT
2
1
2
2
1
2
,
,
a
f
a
f
=+
z
P
.
This is the end of the preview. Sign up
to
access the rest of the document.
This note was uploaded on 10/22/2011 for the course ENG 101 taught by Professor Yukov during the Spring '11 term at UCLA.
 Spring '11
 Yukov

Click to edit the document details